PENENTUAN FREKUENSI PRIBADI PADA GETARAN BALOK KOMPOSIT DENGAN PENGUAT FIBERGLASS - Mustafa Mustafa (Jurnal MEKANIKAL, 2012)
This aim of the study was to experimentally analyze the natural frequency (wn) of fiberglass reinforced polymer composite beam. The study used the spectrum method for experimental analysis. The spectrum method for experimental analysis was done by various position of 5 exciters. The supports used were a fixed-free (cantilever) with the material of fiberglass reinforced polymer composite in the form of beam with length 50 cm, width 3 cm, and thickness 2 cm. Composite material consisted of two compositions that was 5 % of fiberglass and 20 % of fiberglass. The devices used in the study was testing machine, IRD mechanalysis comprising vibration sensor, speed regulation unit, tachometer, and vibrator engine. The measurement was done on deflection, frequency response function, and spectrum. The results of the study obtained : For experimental analysis, at percentage of fiberglass   5 %, value wnmax = 13125 rpm, wnmin = 12600 rpm, whereas the percentage of fiberglass 20 %, value wnmax = 13230 rpm, wnmin = 12990 rpm.